The Pengaruh Pengaplikasian Vacuum Cooling Pasca Pasteurisasi Pada Madu Hutan Riau Terhadap Aktivitas Enzim Diastase dan Sifat Fisik - Silvi Astri Cahyani; Anang Lastriyanto; Sandra Malin Sutan; Sumardi Sumardi (jurnal1, 2021)
Honey is defined as a traditional natural liquid which usually has a sweet taste derived from the nectar of flowers. The main component of honey is a natural saturated sugar solution consisting of a mixture of complex carbohydrates and contains various important micro-nutrients such as vitamins, minerals, enzymes, and organic compounds. These micro-nutrients are very susceptible to damage during the honey processing process. In this study, a cooling method in the form of vacuum cooling was applied with the aim of maintaining the micro-nutrients in honey. Vacuum cooling that is applied after the pasteurization process aims to release the latent heat trapped in the honey in a relatively short time and minimize damage to micronutrient, especially the diastase enzyme. The research design consisted of 2 factors, namely the volume chamber consisting of 12.5%, 25%, and 50%. The second factor is the cooling method which consists of conventional and vacuum cooling. The samples from the research were tested on diastase enzyme activity and the physical properties of honey such as moisture content, density, and acidity. The results showed that cooling with the vacuum cooling method had lower water content, low acidity, high density, and better diastase enzyme activity compared to conventional cooling.